Modelling the role of electron attachment rates on column density ratios for CnH−/CnH (n=4, 6, 8) in dense molecular clouds. (4th October 2016) - Gianturco, F A; Grassi, T; Wester, R
Abstract: The fairly recent detection of a variety of anions in the interstellar molecular clouds have underlined the importance of realistically modelling the processes governing their abundance. To pursue this task, our earlier calculations for the radiative electron attachment (REA) rates for C4 H −, C6 H −, and C8 H − are employed in the present work, within a broad network of other concurrent reactions, to generate the corresponding column density ratios of anion/neutral (A/N) relative abundances. The latter are then compared with those obtained in recent years from observational measurements. The calculations involved the time-dependent solutions of a large network of chemical processes over an extended time interval and included a series of runs in which the values of REA rates were repeatedly scaled over several orders of magnitude. Macroscopic parameters for the Clouds' modelling were also varied to cover a broad range of physical environments. It was found that, within the range and quality of the processes included in the present network, and selected from state-of-the-art astrophysical databases, the REA values required to match the observed A/N ratios needed to be reduced by orders of magnitude for C4 H − case, while the same rates for C6 H − and C8 H − only needed to be scaled by much smaller factors. The results suggest that the generally proposed formation of interstellar anions by REA mechanism is overestimated by current models for the C4 H − case, for which is likely to be an inefficient path to formation. This path is thus providing a rather marginal contribution to the observed abundances of C4 H −, the latter being more likely to originate from other chemical processes in the network, as we discuss in some detail in the present work. Possible physical reasons for the much smaller differences against observations found instead for the values of the (A/N) ratios in two other, longer members of the series are put forward and analysed within the evolutionary modelling discussed in the present work.